Kronik Boyun Ağrılı Hastalarda Bilişsel Egzersiz Terapi Yaklaşımı Ölçeği’nin Geçerlik, Güvenirlik ve Duyarlılığının Belirlenmesi - Şahin, Özge (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
The aim of this study was to determine the validity, reliability, and sensitivity of the Cognitive Exercise Therapy Approach (Bilişsel Egzersiz Terapi Yaklaşımı-BETY) scale in patients with chronic neck pain. The study included 199 patients with chronic neck pain, aged between 18-65 years, with pain severity 3 and above according to the Visual Analogue Scale. Neck Disability Index (NDI), Arm Shoulder and Hand Problems Questionnaire (DASH), Short Form-36 (SF-36), Hospital Anxiety and Depression Scale (HADS) were used to evaluate the validity of the BETY scale. In order to assess the reliability of the BETY Scale, 199 subjects were re-filled 1 week after the initial evaluation. To assess the sensitivity of the scale, 44 subjects were included in a 2-week treatment program. After the treatment, all questionnaires used for validity were replenished to 44 individuals. Of the 199 individuals included in the study, %82,9 were female, %17,1 were male, and the mean age was 45,9 ± 11,1. As a result of the study, the moderate degree between the BETY scale and the NDI (r= 0,64, p<0,001); good degree with DASH (r=0,74, p<0,001), and HADS with anxiety and depression parameters were between moderate (r=0,64, r=0,58, p <0,001, respectively) and the moderate to weak relationship between the sub-parameters of the SF-36 (r= -0,46 to r= -0,61, p<0,001). The reliability of the scale was found to be excellent as a result of the analysis using Cronbach alpha (r=0,997 p<0,001). The in-class reliability coefficient (ICC) (r=0,993, p<0,001) calculated for the reliability of the scale showed that the reliability of the scale was excellent. In addition, the analysis performed using Cronbach alpha (r=0,997, p<0,001) showed that the internal consistency of the scale was quite high. As a result of the analysis made with Wilcoxon, the standardized mean response value of the BETY scale was 2,1 and according to this result, the scale was sensitive.

ÖZ: Bu çalışma, kronik boyun ağrısı olan hastalarda Bilişsel Egzersiz Terapi Yaklaşımı (BETY) ölçeğinin geçerlik, güvenirlik ve duyarlılığının belirlenmesi amacı ile yapıldı. Çalışmaya Görsel Analog Skalasına göre ağrı şiddeti 3 ve üzeri olan, 18-65 yaş arası, 199 kronik boyun ağrılı hasta dahil edildi. BETY ölçeğinin geçerliğini değerlendirmek için Boyun Özür İndeksi (BÖİ); Kol, Omuz ve El Sorunları Anketi (DASH), Kısa Form-36 (KF-36), Hastane Anksiyete ve Depresyon Ölçeği (HADÖ) kullanıldı. BETY ölçeğinin güvenirliğini değerlendirmek için 199 bireye ilk değerlendirmeden 1 hafta sonra BETY ölçeği yeniden uygulandı. Ölçeğin duyarlılığını değerlendirmek için, 44 birey 2 haftalık bir tedavi programına dahil edildi. Tedavi sonrası, geçerlik değerlendirmesi için kullanılan anketlerin tümü 44 bireye yeniden uygulandı. Çalışmaya dahil edilen 199 bireyin %82,9’unun kadın, %17,1’inin erkek olduğu, yaş ortalamalarının 45,9 ± 11,1 olduğu görüldü. Çalışma sonucunda, BETY ölçeğinin, BÖİ ile arasında orta derece (r=0,64, p<0,001); DASH ile arasında iyi derece (r=0,74, p<0,001), HADÖ’nin anksiyete ve depresyon parametreleri ile arasında orta derece (sıra ile r=0,64, r=0,58, p<0,001) ve KF-36’nın alt parametreleri ile arasında (r= -0,46 ile r= -0,61 arasında p<0,001) orta ve zayıf derece bir ilişki olduğu görüldü. Ölçeğin güvenirliği için hesaplanan sınıf içi güvenirlik katsayının (ICC) (r=0,993, p<0,001) 1’e yakın olması ölçeğin güvenirliğinin mükemmel olduğunu gösterdi. Ayrıca Cronbach alfa kullanılarak (r=0,997, p<0,001) yapılan analiz sonucu ölçeğin iç tutarlılığının oldukça yüksek olduğu görüldü. Wilcoxon ile yapılan analiz sonucu BETY ölçeğinin standartlaştırılmış ortalama yanıt değerinin 2,1 olduğu ve bu sonuca göre de ölçeğin duyarlı olduğu görüldü.
Fizyoterapi ve Rehabilitasyon Dalında Yüksek Lisans Tezidir. Tez (Yüksek Lisans)--Doğu Akdeniz Üniversitesi, Sağlık Bilimleri Fakültesi, Fizyoterapi ve Rehabilitasyon Bölümü, 2020. Eş-Tez Danışmanı: Yard. Doç. Dr. Ender Angın ve Tez Danışmanı: Yard. Doç. Dr. Sevim Öksüz.
Keywords: Fizyoterapi ve Rehabilitasyon; Geçerlik; güvenirlik; duyarlılık; kronik boyun ağrısı; Bilişsel Egzersiz Terapi Yaklaşımı Ölçeği; Validity; reliability; sensitivity; chronic neck pain; Cognitive Exercise Therapy Approach Scale